Representasi Wabi Sabi dalam Film Animasi Whisper of the Heart - Rafael Ksatrya Senoputra; Marisa Rianti Sutanto; Ethel Deborah Lewerissa; Jessica Priscilla Nangoi (Indonesian Democracy Research Center, 2026)
Whisper of the Heart is an animated film produced by Studio Ghibli and directed by Yoshifumi Kondou. The film tells the story of a teenager named Shizuku who is searching for her true self. Two other characters who play a significant role in Shizuku’s journey are Seiji and Nishi. In this animated film, Kondou not only portrays the lives of teenagers in general but also weaves in the philosophy of wabi sabi, which has three core values: simplicity, imperfection, and transience. This representation of wabi sabi is reflected through the character development of the protagonists. Simplicity is reflected in the lifestyles of Shizuku, Seiji, and Nishi. Imperfection is reflected through Shizuku’s unstable and indecisive nature. Transience is reflected through the figure of the Baron cat statue and Nishi’s memories of the past. Settings such as the Tama Hills, the train tracks, the library, the Chikyuuya studio, and the violin workshop serve to create a quiet and unadorned atmosphere, thereby reinforcing the reflection of wabi-sabi values in everyday life. The philosophy of wabi-sabi teaches that life is not always smooth and beautiful, but it is in the cracks and imperfections that human values are reflected.